NSV 1440: first WZ Sge-type object in AM CVn stars and candidates. (11th March 2019) - Isogai, Keisuke; Kato, Taichi; Monard, Berto; Hambsch, Franz-Josef; Myers, Gordon; Starr, Peter; Cook, Lewis M; Nogami, Daisaku
Abstract: In 2015 and 2017, the AM CVn candidate NSV 1440 showed superoutbursts that had the characteristic features of WZ Sge-type dwarf novae (DNe). By analogy with hydrogen-rich cataclysmic variables (CVs), we can interpret these outbursts as "double superoutbursts" which are composed of a first superoutburst with early superhumps and a second superoutburst with ordinary superhumps. The object also showed multiple rebrightenings after the main superoutbursts. Early superhumps had never before been observed in AM CVn stars and candidates, thus NSV 1440 is the first confirmed WZ Sge-type AM CVn candidate. We obtained an early superhump period of 0.0252329(49) d and a growing (stage A) superhumps period of 0.025679(20) d from the 2015 superoutburst. We regarded the early superhump period as the orbital one. By using these periods we estimated the mass ratio q = 0.045(2). This value suggests that NSV 1440 is indeed an AM CVn star and that the secondary is a semi-degenerate star.